Women and Redemption : A Theological History, Second Edition - Ruether, Rosemary Radford (Book collections on Project MUSE., 2012)
"Rosemary Radford Ruether's authoritative, award-winning critique of women's unequal standing in the church, which explored the complex history of redemption in evaluating conflict over the fundamental meaning of the Christian gospel for gender relations, is now in an updated and expanded edition. Ruether highlights women theologians' work to challenge the patriarchal paradigm of historical theology and to present redemption linked to the liberation of women. Ruether turns her attention to the situation of women globally and how the growing plurality of women's voices from multicultural and multireligious contexts articulates feminist liberation theology today."--Publisher description